Low Carbon Development of China’s Yangtze River Delta Region - Shan, Shengdao; Bi, Xiaohang (Problemy Ekorozwoju, 2012)
Low carbon development is a development pattern to enable social and economic progress along the path of sustainable development. This paper analyzes the low carbon development situation and trend in the China’s Yangtze River Delta region, one of the most important industrial and economic centers of China. The results indicate low carbon development in this region continues to move forward. However, many barriers, such as unbalanced energy consumption structure and limited research and development capability still exist. Some solutions to overcoming the barriers are proposed in the paper, covering policy, strategic, technological, educational measures.